Modernising consumer markets: a response to the consumer green paper - Cartwright, Peter; Dunleavy, Sam; Hyde, Richard (Centre for Commercial Law, University of Notttingham, 2018)
A response to the BEIS Green Paper Modernising Consumer Markets by Peter Cartwright, Sam Dunleavy and Richard Hyde who are Consumer Law and Policy specialists at the Centre for Commercial Law in the School of Law at the University of Nottingham.